Physical Properties of Concrete Roof Tiles Containing Recycled Wood-wool and Quarry Dust as Partial Sand Replacement - Johalmi, Nurmizatul Aneesa; Md Noh, Mohammad Soffi (Recent Trends in Civil Engineering and Built Environment, 2025)
Concrete roof tile is an important building material that highly demanding in construction sector. The production of wood-wool concrete roof tiles (WWCRT) become an alternative in generating sustainable material development and have its potential to be in demanding market. WWCRT was a prototype of flat roof contained grinded wood wool (CWWP) and quarry dust as partial sand replacement with the addition of perlite and SP. The aim of this study is to investigate the physical properties of WWCRT mortar and to identify the optimum proportion of replacement material, water-cement ratio and mix proportion of roof tile. The tests conducted were water absorption of prism-shape mortar and water permeability of WWCRT mortar. The results showed that the B15 of WWCRT mix with 15% and 10% proportion of CWWP and QD respectively achieved the lowest water absorption rate which is 9.9% and this is the optimum percentage in producing a low-density roof mortar as its density of 28-day of curing is 1567 kg/m3. For water permeability rate by uncoated WWCRT, B15 showed the lowest rate as the water seeping in 1-hour test only up to 38 mm depth. WWCRT with surface coating enhanced the performance of this test as all coated roof batches resulted nearly null of water permeability rate. Therefore, the proportion of CWWP and QD affected the physical behaviour of mortar.